Improvement of heat resistance of silica-agglomerate electret using electrostatic spraying - Chenye WU; Kensuke KAGEYAMA; Tatenobu SAKAI (Mechanical Engineering Journal, 2015)
The silica-agglomerate electret could be obtained after spraying negatively charged solution of colloidal silica on a fluororesin film using an electrostatic spraying technique. The surface electric potential was measured after spraying to investigate which method was suitable for preparing the electret. As a result, the method in which a spray gun was installed to a conventional corona-charging setup delivered the electret with the amplitude of the electric surface potential over 0.8 kV. The silica agglomerates using an electrostatic spraying technique (ES electret) showed larger diameter D and lower point density N than those using conventional technique (corona-charging after spraying, CC electret). Furthermore, the prepared electrets were heated to examine the improvement of the heat resistivity by the electrostatic spraying. Then, the obtained silica-agglomerate electret showed better heat resistivity than the conventional silica-agglomerate electret. Then, the charge retention at 250°C R250 of ES electrets prepared in this study was higher than 57 % when the electrets suffered high temperature from 200 to 250 °C for 12.5 min at the heating test. Consequently, it can be concluded that the electrostatic spraying was excellent technique to obtain the silica-agglomerates electret with high heat resistance.